2007
DOI: 10.1073/pnas.0704662104
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting biological “dark matter” with single-cell genetic analysis of rare and uncultivated TM7 microbes from the human mouth

Abstract: We have developed a microfluidic device that allows the isolation and genome amplification of individual microbial cells, thereby enabling organism-level genomic analysis of complex microbial ecosystems without the need for culture. This device was used to perform a directed survey of the human subgingival crevice and to isolate bacteria having rod-like morphology. Several isolated microbes had a 16S rRNA sequence that placed them in candidate phylum TM7, which has no cultivated or sequenced members. Genome am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
538
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 558 publications
(542 citation statements)
references
References 26 publications
(36 reference statements)
4
538
0
Order By: Relevance
“…Consequently, current genome repositories are not representative of the microbial diversity known from 16S rRNA gene surveys 4 . Concerted efforts are being made to address this limitation by target ing phylogenetically distinct microorganisms for cultivation [5][6][7] and single-cell sequencing 4,8 . Although these approaches continue to provide valuable reference genomes, the former is restricted to microorganisms amenable to cultivation and the latter is hampered by technical challenges and the need for specialised equipment 9 .…”
mentioning
confidence: 99%
“…Consequently, current genome repositories are not representative of the microbial diversity known from 16S rRNA gene surveys 4 . Concerted efforts are being made to address this limitation by target ing phylogenetically distinct microorganisms for cultivation [5][6][7] and single-cell sequencing 4,8 . Although these approaches continue to provide valuable reference genomes, the former is restricted to microorganisms amenable to cultivation and the latter is hampered by technical challenges and the need for specialised equipment 9 .…”
mentioning
confidence: 99%
“…However, current developments in cultivation methodologies [43] and DNA amplification from single cells [44], combined with highthroughput cell sorting, will probably push single-genome sequencing to environmental scales and will allow us to avoid some of the weaknesses of metagenomics data [45]. Single-genome sequencing is therefore likely to be the input data source of choice for this type of analysis in the near future [46][47][48][49].…”
Section: Metabolic Cooperationmentioning
confidence: 99%
“…However, current developments in cultivation methodologies [43] and DNA amplification from single cells [44], combined with highthroughput cell sorting, will probably push single-genome sequencing to environmental scales and will allow us to avoid some of the weaknesses of metagenomics data [45]. Single-genome sequencing is therefore likely to be the input data source of choice for this type of analysis in the near future [46][47][48][49].Many examples of the collaboration and cooperation of microorganisms, including the formation of complex consortia or biofilms and cell-cell communication, seem to occur at micrometre-range distances in open systems [50]. Therefore, analogous to protein complexes in cellular systems biology, the observation of physical cell-cell interactions between organisms provides strong indications of functional interactions in the ecosystem network.…”
mentioning
confidence: 99%
“…Metagenomic analyses have shown the metabolic potential of some groups, i.e., OD1 (Wrighton et al 2012), OP1 (Takami et al 2012), TM6 (McLean et al 2013) and TM7 (Marcy et al 2007). Furthermore, a recent study has reported the near-complete genomes of GN02, OP3, SAR406 and WS3, in addition to OD1 and OP1, using single-cell genomic analysis; however, details of metabolic potential have not been described yet (Rinke et al 2013).…”
Section: Uncultured Bacterial Clone Groupsmentioning
confidence: 99%